Diallel Analysis of Chili (Capsicum annuum L.) Resistance to Phytophthora capsici Leonian - Rahmi Yunianti (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2011)
To accomplish the study of genetic parameters of chili resistance to P. capsici, thirty cross combinations from six parents’ crosses were made by full diallel method. The resistance was assessed based on the incidence of disease, following the inoculation of 28 days-old plant of chili. Inoculation was done by dropping 5 mL of inoculum (105 zoospore mL-1) at the base part of each plant. There was non-allelic interaction and overdominance effect. Chili resistance to P. capsici controlled by one positive gene. The parents contained more dominant gene, with dominance order were IPB-C4, IPB-C10, IPB-C15, IPB-C9, IPB-C8, and IPB-C2. The prediction of the possible limits of selection if homozygote genes assemble on one individual was 0.676-0.691. Broad-sense and narrow-sense heritability values for the traits were high. Keywords: chili, diallel analysis, genetic parameter, Phytophthora capsici